Response of drip irrigated Spinach, Radish and Onion under variable irrigation - SHERRING, ARPAN; SINGH, VIKRAM (Journal of Soil and Water Conservation, 2021)
Field experiments were conducted at the irrigation research farm of Allahabad Agricultural Institute- Deemed University, Allahabad, India during the crop growing season of November- February on clay loam soil in order to evaluate the effect of five irrigation levels (25, 75, 125, 175 and 225% of Pan Evaporation Replenishment) on yield, irrigation production efficiency and economic return of spinach, radish and onion under semi arid climate. The highest mean marketable yield of spinach (21.48 t/ha), radish (19.56 t/ha) & onion (33.07 t/ha) was recorded at 175 % of pan evaporation replenishment. A further increase in irrigation amount resulting from 225% of pan evaporation replenishment reduced the marketable yield of spinach, radish and onion. The mean irrigation production efficiency for spinach, radish and onion was significantly higher with irrigation at 25 % of pan evaporation replenishment and it decreased with the increase in irrigation level. Irrigation at 175 % of pan evaporation replenishment resulted in highest net return of spinach (Rs 53314.89/ha), radish (Rs 71125.09/ha) and onion (Rs 187410.49/ ha). A further increase in irrigation resulting from 225% of pan evaporation replenishment reduced the net return of spinach, radish and onion. The seasonal water applied and marketable yield of spinach, radish and onion showed strong quadratic relationship (R2 = 0.935 - 0.992), which can be used with no constraints of available land and the corresponding irrigation application and scheduling for optimizing economic return for these crops in the region.